Numerical treatment of a magnetized electron fluid model in a 3D simulator of plasma thruster plumes - Modesti, Alberto; Cichocki, Filippo; Ahedo, Eduardo (Frontiers in Physics, 2023)
Simulations of energetic plumes from plasma thrusters are of great interest for estimating performances and interaction with the spacecraft. Both in fully-fluid or hybrid (particle/fluid) models, the electron population is described by a set of fluid equations whose resolution by different numerical schemes can be strongly affected by convergence and accuracy issues. The case of magnetized plumes is more critical. Here, the numerical discretization of the electron fluid model of a 3D hybrid simulator of plasma plumes was upgraded from a Finite Differences (FD) formulation in a collocated grid, to a Finite Volumes (FV) approach in a staggered grid.Both approaches make use of structured meshes of different resolutions and are compared in two scenarios of interest: (i) an unmagnetized plasma plume around a spacecraft, and (ii) a magnetized plume expansion in free space. In both physical scenarios, the FD scheme exhibits a global continuity error related to truncation errors that can be reduced only by refining the mesh.The origin of this error is here further investigated and explained. The FV scheme instead can save much computational time by using coarser meshes, since it is free of those errors due to the conservativeness of its formulation. The physical advantage of the FV scheme over the FD one is more evident for magnetized plumes with high Hall parameters, since it allows to reach higher anisotropy conditions, here assessed in order to gain insight into plume magnetization effects.